Determinants of micronutrient supplementation during pregnancy among women in three sub-Saharan African countries: a multilevel logistic regression model - Mekonen, Enyew Getaneh; Zegeye, Alebachew Ferede; Workneh, Belayneh Shetie; Ali, Mohammed Seid; Gonete, Almaz Tefera; Alemu, Tewodros Getaneh; Tamir, Tadesse Tarik; Tekeba, Berhan; Wassie, Mulugeta; Kassie, Alemneh Tadesse (Frontiers in Global Women's Health, 2024)
BackgroundPoor maternal nutrition during pregnancy is a common cause of poor maternal and infant outcomes. Micronutrient deficiencies are common among pregnant women in low- and middle-income countries, including sub-Saharan Africa. Pregnant women are recommended to take micronutrients like iron or folic acid and deworming medication during pregnancy. Therefore, this study was conducted to assess micronutrient intake and its associated factors among pregnant women in three countries using the most recent demographic and health survey.MethodsWe used data from the most recent demographic and health surveys, which were carried out between 2019 and 2022 in three sub-Saharan African countries. The study included a weighted sample of 13,568 reproductive-age women who had given birth within the five years prior to the survey. Utilizing multilevel logistic regression, the factors associated with the dependent variable were identified. Model comparison and fitness were assessed using the deviance (-2LLR), likelihood ratio test, median odds ratio, and intra-class correlation coefficient. Ultimately, factors were deemed statistically significant if they had a p-value less than 0.05.ResultsThe pooled prevalence of micronutrient intake among pregnant women during pregnancy of last birth was 77.56% (95% CI: 76.85%–78.25%). Factors like age [AOR = 1.78; 95% CI (1.14, 2.77)], educational status [AOR = 1.49; 95% CI (1.23, 1.79)], marital status [AOR = 0.66; 95% CI (0.58, 0.75)], working status [AOR = 1.17; 95% CI (1.01, 1.34)], media exposure [AOR = 1.20; 95% CI (1.05, 1.38)], preceding birth interval [AOR = 1.17; 95% CI (1.01, 1.34)], number of ANC visits [AOR = 1.65; 95% CI (1.29, 2.10)], and residence [AOR = 1.19; 95% CI (1.03, 1.37)] were significantly associated with micronutrient intake among pregnant women.ConclusionsMore than three-fourths of the study subjects were micronutrient supplemented during their pregnancy. Improving women's education, disseminating nutrition information through media, providing more attention to young pregnant women who live in rural areas, increasing the number of ANC visits, and women's empowerment are strongly recommended.